The women, gender and development reader - Visvanathan, Nalini, 1945- (Halifax : Fernwood Pub. ; London ; New York : Zed Books Ltd. ; New York : Distributed in the USA exclusively by Palgrave Macmillan, 2011)
"In this fully revised second edition, the editors expertly present the impact of social, political and economic change by reviewing such topical issues as migration, persistent structural discrimination, the global recession and climate change. With a multidisciplinary approach, the volume vividly illustrates the theoretical debates with an array of case studies from around the world"--P. [4] of cover.
History of international development, theories and discourse of women, gender and development -- Households, families and work -- Women in the global economy -- International women in social transformation -- Women organizing themselves for change : transnational movements, local resistance.
First ed. published: 1997.
Includes bibliographical references and index.
Keywords: Women -- Developing countries -- Social conditions; Women -- Developing countries -- Economic conditions; Women in development